Investigation of the effect of flipped listening instruction on the listening performance and listening anxiety of Chinese EFL students - Qiu, Yu; Luo, Wei (Frontiers in Psychology, 2022)
Introduction Given the fact that flipped instruction especially with the aid of technology has gained momentum in second language (L2) instruction, numerous L2 researchers have explored the usefulness of flipped classroom for L2 learning. Methods As an attempt to further this research area, the current research examined the effect of flipped listening instruction on the Chinese English as a foreign language (EFL) students’ listening performance and listening anxiety using a quasi-experimental research design. To this end, a total number of 44 EFL learners from two intact classes in a Chinese language school were selected as the participants of the research and they were randomly assigned as the control group (N = 21) and an experimental group (N = 23). Within a course of one semester, the control group was instructed employing traditional listening instruction, while the experimental group were taught based on the flipped mode of instruction. Results The data collection was carried out by administering the listening section of IELTS and Foreign Language Listening Anxiety Scale (FLLAS). Discussion The results of ANCOVA revealed that the flipped listening instruction significantly enhanced listening performance of the participants. Also, the flipped classroom substantially reduced listening anxiety of the EFL learners. The outcomes of this research might provide notable implications for EFL practitioners.